Effects of the chymase inhibitor fulacimstat on adverse cardiac remodeling after acute myocardial infarction-Results of the Chymase Inhibitor in Adverse Remodeling after Myocardial Infarction (CHIARA MIA) 2 trial - Duengen, Hans-Dirk; Kim, Raymond J; Zahger, Doron; Orvin, Katia; Kornowski, Ran; Admon, Dan; Kettner, Jiri; Shimony, Avraham; Otto, Christiane; Becka, Michael; Kanefendt, Friederike; Romo, Andres Iniguez; et al. (The American heart journal, 2020)
BACKGROUND: Adverse cardiac remodeling is a major risk factor for the development of post myocardial infarction (MI) heart failure (HF). This study investigates the effects of the chymase inhibitor fulacimstat on adverse cardiac remodeling after acute ST-segment-elevation myocardial infarction (STEMI). METHODS: In this double-blind, randomized, placebo-controlled trial patients with first STEMI were eligible. To preferentially enrich patients at high risk of adverse remodeling, main inclusion criteria were a left-ventricular ejection fraction (LVEF) ≤45% and an infarct size >10% on day 5 to 9 post MI as measured by cardiac MRI. Patients were then randomized to 6 months treatment with either 25 mg fulacimstat (n = 54) or placebo (n = 53) twice daily on top of standard of care starting day 6 to 12 post MI. The changes in LVEF, LV end-diastolic volume index (LVEDVI), and LV end-systolic volume index (LVESVI) from baseline to 6 months were analyzed by a central blinded cardiac MRI core laboratory. RESULTS: Fulacimstat was safe and well tolerated and achieved mean total trough concentrations that were approximately tenfold higher than those predicted to be required for minimal therapeutic activity. Comparable changes in LVEF (fulacimstat: 3.5% ± 5.4%, placebo: 4.0% ± 5.0%, P = .69), LVEDVI (fulacimstat: 7.3 ± 13.3 mL/m2, placebo: 5.1 ± 18.9 mL/m2, P = .54), and LVESVI (fulacimstat: 2.3 ± 11.2 mL/m2, placebo: 0.6 ± 14.8 mL/m2, P = .56) were observed in both treatment arms. CONCLUSION: Fulacimstat was safe and well tolerated in patients with left-ventricular dysfunction (LVD) after first STEMI but had no effect on cardiac remodeling.
Keywords: tepový objem; magnetická rezonance kinematografická; Humans; Heart Failure; Stroke Volume; srdeční selhání; lidé středního věku; funkce levé komory srdeční; Ventricular Remodeling; Double-Blind Method; Female; infarkt myokardu s elevacemi ST úseků; Chymases; výsledek terapie; dvojitá slepá metoda; lidé; ST Elevation Myocardial Infarction; chymasy; ženské pohlaví; Male; Magnetic Resonance Imaging, Cine; Middle Aged; Treatment Outcome; Heart Ventricles; mužské pohlaví; remodelace komor; srdeční komory; Ventricular Function, Left